"Decomposition Of Metal Sulfates - A SO2 -Source For Sulfuric Acid Production" - Abstract And Introduction (The Southern African Institute of Mining and Metallurgy, 2009)
The peak in Sulphur price late 2008 caused again intensified investigation into the decomposition of sulphates and spend acid. One option is the recycling of sulphur from spend acid, which already started more than 40 years ago in the field of spend acid from organic processes in refineries and acrylic glass manufacturing. Since this acid couldn't be neutralized and discarded due to high organic contents, another source of SO2 to produce sulfuric acid is the decomposition of metal sulfates. The decomposition of metal sulfates was investigated at the next peak in Sulphur price in the 80?s. The first major scale pilot tests and studies of gypsum decomposition were carried out for clients in Florida. The decomposition of gypsum was quite often mainly influenced by the strategic decision of some countries to get own and independent acid production. In other cases the industry doesn?t have enough space to dump the gypsum. Therefore the company was also forced to convert the gypsum into ?saleable? products to avoid these residues. Other projects were made for the recycling of iron-sulfates from the pigment industry. The motivations for these projects were not only given by acid price. For the German pigment industry it was no longer permitted in the 80?s to dump the iron sulphate residues into the sea. These regulations forced the industry to develop new technology, which allows converting of the FeSO4-residues into iron oxide and acid. Therefore economical and mainly environmental factors influenced the decision of the companies to develop and to build these plants. Beside the above mention iron- and calcium-sulphates many other process exist, which produce metal sulphates as an intermediate product. These cases are not forced by environmental or strategic factors. In cases like Ni, Co or Mn-decomposition the main product of the plant is treated in the decomposition plant and later on used as ferrous-alloys. These final products are higher in price compared to e.g. CaO, which exclude the high-energy consumption for the endothermic chemical decomposition reaction. The reaction of SO2 generation based on acid or sulfate decomposition takes place in the range of 1000°C. The energy demand of the endothermic reaction is considerable and leads due to the high fuel-combustion off-gas stream to a diluted SO2 gas. Energy prices are usually increasing at the same time like sulphur. Sulphuric Acid based on decomposition is therefore more expensive than as acid based on sulphur combustion. The paper describes fluid bed technology and possible process concepts for decomposition plants. Additionally the thermodynamic background of the decomposition process and the main influence factors are provided to receive a better understanding of this technology.